Caracterización magnética y datación preliminar mediante paleointensidades relativas de sedimentos lacustres de la Formación Tajamar (Guachipas), Salta Argentina - Irurzun, Maria Alicia (2014)
This paper presents a detailed study of rock magnetism in lacustrine sediments from three sample sequences from the Pleistocene Tajamar Formation, exposed in an outcrop near the locality of Guachipas (25º31.0´S 65°30.5'W), in Salta Province, Argentina. The studied sediments are located in the drainage of the Guachipas River, which drains Meso-Cenozoic outcrops that border the southern end of the Lerma Valley.The studied samples showed a stable remanent magnetization that was obtained after removing a viscous remanent magnetization with alternating fields of about 10-15 mT. The magnetic properties indicate that the main carrier of remanence is magnetite with the presence of hematite in different percentages. Magnetite samples have magnetic grain sizes between 4 and 16 mm. The magnetic concentration parameters have the same variations as the stable remanent magnetization suggesting the signal is dominated by this magnetic parameter. Based on this, the relative paleointensities were calculated using the normalization method. In order to obtain an approximate age for the deposits, the relative paleointensity curve of Guachipas was compared with the SINT800 curve using different correlation windows. The best correlation was obtained with the window 40 - 200 ky BP.